KAJIAN TEKNOLOGI SISTEM UJIAN ONLINE DENGAN MENGGUNAKAN MODEL UTAUT - Nunung Hidayatun (Paradigma, 2013)
Online examination system is the system of evaluation of student learning online through thewebsite. This study aims to determine the acceptance of the use of technology in onlineexamination system and the factors that influence the model Unified Theory Of Acceptance AndUse Of Technology (UTAUT) that have been modified. Statistical test methods Structural EquationModeling (SEM) that will be analyzed using AMOS software, so expect the research the institutionget information related to the factors that influence the attitudes and behavior of the users ofonline exam system. From the results of SEM analysis found that the model did not fit. Therefore,the use of analysis. The factors that influence it are performance expectancy, and social influence,explain 42.9% of the variance.Keywords: Unified Theory Of Acceptance And Use Of Technology (UTAUT), Online Testing System.